Telestroke in Resource-Limited Settings: Systematic Review of Clinical Outcomes and Barriers - Akbar Wibriansyah; Laras Wiyardhani; Tara Sander (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: Stroke disproportionately affects resource-limited settings, where delayed access to specialist neurological evaluation limits eligibility for time-critical reperfusion therapies. Objectives: This review aimed to evaluate the clinical outcomes, workflow efficiency, and implementation barriers associated with telestroke in resource-limited settings, thereby informing evidence-based strategies to improve equitable stroke care. Methods: This systematic review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. PubMed, Scopus, and the Cochrane Library were searched for studies published between 2005 and 2025 that evaluated telestroke implementation in resource-limited settings. Eligible studies included randomized and observational designs reporting clinical outcomes, workflow metrics, or safety indicators. Due to substantial heterogeneity in study designs and outcome reporting, the findings were synthesized narratively. Results: Ten studies involving 13,786 patients were included. Across studies, telestroke was consistently associated with shorter door-to-needle and door-to-imaging times, higher rates of intravenous thrombolysis administration, and increased referrals for endovascular therapy. Several observational studies reported lower mortality rates in telestroke-supported care, whereas functional outcomes at 90 days demonstrated inconsistent findings. No study reported an increased risk of symptomatic intracranial hemorrhage. Conclusion: Available evidence suggests that telestroke implementation in resource-limited settings may improve acute stroke workflow and access to reperfusion therapies without compromising safety, although improvements in functional outcomes remain limited. Telestroke represents a feasible strategy for enhancing equity in stroke care; however, broader system-level investment, infrastructure development, and rehabilitation capacity remain essential.